COME-Invoicing: Digital solution for invoice management in small businesses - Wong, Sum Hui (2025)
The COME-Invoicing application aims at helping hawkers and small businesses in Malaysia to survive and assimilate in the government adopted e-invoicing system. This mobile application solves problems like low levels of technology adoption, compliance with stringent e-invoicing rules, and the lack of automation in sales tracking. Thus, the application allows users with low IT literacy to better navigate the recording of daily sales, generate automatic reports for the month, and even receive real-time information about what measures they need to fulfil requirements imposed by the government. The app also features sophisticated functionalities such as Optical Character Recognition (OCR) which utilizes the Artificial Intelligence technology to digitize handwritten and the voice to text feature that enables capturing of sales data from spoken words. Combined with multilingual support and the ability to educate users of the application, these attributes make a product comprehensible and easy to navigate for small business owners and managers. The proposed solution not only improves the performance and compliance of businesses but also assists the users to transform and learn about Artificial Intelligence and digitization to succeed the existing digital economy of Malaysia. The use of the COME-Invoicing app itself also conforms with Agile development, enabling constant adjustments in the features and designs based on users’ requirements and shifts in regulations. Therefore, the COME-Invoicing application which will be developed through this project will try to support small business and overcome the digital divide in Malaysia.